linguistic features of english texts introducing transport services - Huỳnh Thị Anh Trâm (ĐHĐN., 2015)
This study aims at examining linguistic features of English Texts Introducing Transport Services (ETITSs). The data for analysis in this thesis are 108 samples of ETITSs collected from the official websites of well-known transport companies in three English-speaking countries namely the United States, the United Kingdom and Australia. The study was conducted based on the combination of a variety of methods such as descriptive, analytic and inductive ones. The study focuses on analyzing linguistic features of ETITSs in terms of their syntactic features, lexical choices, cohesive devices and stylistic devices. The findings of this study are clearly presented based on a survey of 108 English Texts Introducing Transport Services. With regard to syntactic features, relative clauses, the passive voice and imperative sentences are the most striking structures in ETITSs. Furthermore, descriptive adjectives, proper nouns and the commissive verbs are prominent lexical choices in ETITSs. In addition, the investigation of cohesive devices reveals that reference, conjunction and repetition are the devices employed with a high frequency. Finally, the stylistic devices commonly used in ETITSs are hyperbole and rhetoric questions. On the basis of the findings, some practical implications for teaching and learning English are suggested. The study provides a better insight into linguistic features of texts in general as well as English Texts Introducing Transport Services in particular. It is hoped that the findings of this thesis will be useful for those who are interested in texts, especially English Texts Introducing Transport Services.